2005
DOI: 10.1080/03670240500187369
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A Intake and Factors Influencing it Amongst Children and Caretakers in Kosrae, Micronesia

Abstract: A cross-sectional study was undertaken in Kosrae, Federated States of Micronesia to assess preschool children and caretaker dietary intake of vitamin A (VA) (including provitamin A carotenoids) and other nutrients contributing to VA status and to investigate relationships between VA intake and factors affecting dietary intake. Ethnography, food sample analysis, two Acknowledgement is made to The University of Queensland for provision of the International Postgraduate Ecology of Food and Nutrition 2005.44:307-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“… Consuming imported food was regarded as a sign of wealth and status by participants Englberger et al . [ 55 ] Kosrae 267 children aged 24–59 months and their caretakers 65 children aged 24–59 months and their caretakers Cross sectional study: 34-item 7-day FFQ Three non-consecutive 24 h dietary recall questionnaires Intake of total Vitamin A, retinol and protein (g). Sources of vitamin A Main dietary components included imported products of rice, flour, chicken, other meats and tinned fish and local products of breadfruit, banana, taro, fish and other seafood.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Consuming imported food was regarded as a sign of wealth and status by participants Englberger et al . [ 55 ] Kosrae 267 children aged 24–59 months and their caretakers 65 children aged 24–59 months and their caretakers Cross sectional study: 34-item 7-day FFQ Three non-consecutive 24 h dietary recall questionnaires Intake of total Vitamin A, retinol and protein (g). Sources of vitamin A Main dietary components included imported products of rice, flour, chicken, other meats and tinned fish and local products of breadfruit, banana, taro, fish and other seafood.…”
Section: Resultsmentioning
confidence: 99%
“…In Kosrae, a cross-sectional survey of children and their caretakers reported that local fish was the second most commonly consumed source of protein, after cooked chicken [ 55 ]. Mean intake of protein, both for children and adults, was above the average requirements, as defined by Latham [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If only a single nutrient or class of nutrient is of interest then data need only be collected on those foods that are a source of that nutrient. For example, this technique has been used in assessing intake of vitamin A 14 and of food allergens 15 . These shortened FFQs cannot be used to assess energy intake, however, and this is a major drawback.…”
Section: Methods Of Measuring Dietmentioning
confidence: 99%
“…Forsythe and Gage 20 describe a method of using focus groups to determine appropriate nomenclature, methods of preparation and cooking used in a multicultural community. Similar methods were used by Englberger and colleagues 14 in Micronesia to identify foods and beverages contributing to vitamin A intake. Other methods include undertaking diet histories of a sample of people living in the study area or using food disappearance data if available in the area.…”
Section: Important Considerations When Choosing a Methods Of Dietary Amentioning
confidence: 99%